Surveillance for SARS‐CoV‐2 and its variants in wastewater of tertiary care hospitals correlates with increasing case burden and outbreaks. Issue 2 (9th January 2023) - Acosta, Nicole; Bautista, Maria A.; Waddell, Barbara J.; Du, Kristine; McCalder, Janine; Pradhan, Puja; Sedaghat, Navid; Papparis, Chloe; Beaudet, Alexander Buchner; Chen, Jianwei; Van Doorn, Jennifer; Xiang, Kevin; et al.
Abstract: Wastewater‐based SARS‐CoV‐2 surveillance enables unbiased and comprehensive monitoring of defined sewersheds. We performed real‐time monitoring of hospital wastewater that differentiated Delta and Omicron variants within total SARS‐CoV‐2‐RNA, enabling correlation to COVID‐19 cases from three tertiary‐care facilities with >2100 inpatient beds in Calgary, Canada. RNA was extracted from hospital wastewater between August/2021 and January/2022, and SARS‐CoV‐2 quantified using RT‐qPCR. Assays targeting R203M and R203K/G204R established the proportional abundance of Delta and Omicron, respectively. Total and variant‐specific SARS‐CoV‐2 in wastewater was compared to data for variant specific COVID‐19 hospitalizations, hospital‐acquired infections, and outbreaks. Ninety‐six percent (188/196) of wastewater samples were SARS‐CoV‐2 positive. Total SARS‐CoV‐2 RNA levels in wastewater increased in tandem with total prevalent cases (Delta plus Omicron). Variant‐specific assessments showed this increase to be mainly driven by Omicron. Hospital‐acquired cases of COVID‐19 were associated with large spikes in wastewater SARS‐CoV‐2 and levels were significantly increased during outbreaks relative to nonoutbreak periods for total SARS‐CoV2, Delta and Omicron. SARS‐CoV‐2 in hospital wastewater was significantly higher during the Omicron‐wave irrespective of outbreaks. Wastewater‐based monitoring of SARS‐CoV‐2 and its variants represents a novel tool for passive COVID‐19 infection surveillance, case identification, containment, and potentially to mitigate viral spread in hospitals.